Crowd-Based Accountability: Examining How Social Media Commentary Reconfigures Organizational Accountability - Karunakaran, Arvind; Orlikowski, Wanda J.; Scott, Susan V. (Organization Science, 2022)
Organizational accountability is considered critical to organizations’ sustained performance and survival. Prior research examines the structural and rhetorical responses that organizations use to manage accountability pressures from different constituents. With the emergence of social media, accountability pressures shift from the relatively clear and well-specified demands of identifiable stakeholders to the unclear and unspecified concerns of a pseudonymous crowd. This is further exacerbated by the public visibility of social media, materializing as a stream of online commentary for a distributed audience. In such conditions, the established structural and rhetorical responses of organizations become less effective for addressing accountability pressures. We conducted a multisite comparative study to examine how organizations in two service sectors (emergency response and hospitality) respond to accountability pressures manifesting as social media commentary on two platforms (Twitter and TripAdvisor). We find organizations responding online to social media commentary while also enacting changes to their practices that recalibrate risk, redeploy resources, and redefine service. These changes produce a diffractive reactivity that reconfigures the meanings, activities, relations, and outcomes of service work as well as the boundaries of organizational accountability. We synthesize these findings in a model of crowd-based accountability and discuss the contributions of this study to research on accountability and organizing in the social media era.